SOCIAL CAPITAL ON THE BROILERS BUSINESS PARTNERSHIP SYSTEM - Utami, Sri Wira; Mutmainnah, Mutmainnah; Hakim, Mita Arifah; Qinayah, Mirnatul; Raisa, Daeva Mubarika (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
The broiler chicken farming partnership system often faces various challenges, one of which is the lack of social capital between the parties involved. This research aims to find out how social capital (trust, network, reciprocity, and norms) in the partnership system of broiler chicken breeders and PT. X. The type of research used is descriptive quantitative. The research population is all breeders who have a partnership with PT. X as many as 39 breeders were used as samples. Data collection was carried out through interviews with the help of a questionnaire. The data analysis used in this research is descriptive statistics using a frequency distribution table. The research results show that social capital (trust, network, reciprocity, and norms) in the partnership system between broiler chicken breeders and PT. X Makassar Branch, namely for mutual trust the score obtained was 75.8 in the unfavorable category, the norms score obtained was 76.6 in the unfavorable category, the network score obtained was 76 in the unfavorable category and the reciprocity score obtained was namely 79.6 in the good category. Thus, the element of social capital has not been implemented well, so it is necessary to apply social capital for the sustainability of the long-term partnership system, because social capital is the glue in a partnership relationship that binds plasma and the core. Social capital in livestock farming communities is influenced by various factors including government institutions, cooperatives, cultural values, and technology. Social capital significantly impacts livestock productivity, business sustainability, and social life. It enhances production, resource efficiency, and product quality. It also contributes to long-term risk management and enhances life satisfaction, participation in social activities, and social support.